An Analysis of Teachers’ Oral Feedback in EFL Classroom Interaction at SMP Negeri 10 Batam - Mega Yulia; Yetti Zainil (Universitas Negeri Padang, 2021)
The present research aims to figure out (1) types of oral feedback used by teachers’ in EFL classroom interaction (2) teachers’ reasons for using oral feedback in EFL classroom interaction, and (2) students’ perceptions about teachers’ oral feedback in EFL classroom interactions. The study employed qualitative descriptive research with the three teachers of SMP Negeri 10 Batam and also students for grade seven, eight and nine as the participants. Observation and Stimulated Recall Interview (SIR) were used to conduct the data, and the data were analysed by using thematic analysis (Braun & Clarke, 2006). The result of this research showed that the teachers used 6 types of oral feedback, namely correction, recast, clarificationrequest, metalinguistic feedback, elicitation and repetitionfrom the theory of (Lightbown and Spada, 1999). However, the average of teachers’ oral feedback use showed a low percen teachers employed oral feedback because of teachers’ responsibility and obligation to provide it, the effective and efficient feedback mode, the utility of oral feedback, positive effect to students, and consequences of none of oral feedback.Through a stimulated recall interview, the teachers admitted that they are still not optimal in providing input to the students. Mostly, the perceived positively to oral feedback. Some students found felt sensitive to oral feedback. Nevertheless, they still realized to its positive effect on the result of their work or performance